Effects of SARS‐CoV‐2 Pandemic on the Mental Health of Spanish Ob‐Gyn Specialists—A Nationwide Study - González-Mesa, Ernesto Santiago; Jiménez-López, Jesús Salvador; Blasco‐Alonso, Marta; Anderica‐Herrero, Jose Ramon; Lubián‐López, Daniel (MDPI, 2021)
It has been reported that frontline health professionals have suffered from an increased rate of mental disorders as a consequence of the SARS-CoV-2 pandemic. Objective: This study aims to evaluate the impact of the pandemic on the mental health of Spanish specialists in the obstetrics and gynecology fields after the fifth Spanish COVID-19 wave. Methods: Psychometric screening of the professionals was performed using a nationwide online survey designed by the Psychosocial Obstetrics and Gynecology taskforce. Post-traumatic stress disorder (PTSD), depression, and general anxiety disorder were screened. Results: We found high scores for PTSD, depression, and generalized anxiety disorder. Up to 12.4% of specialists met the PTSD criteria, 12.8% showed complex PTSD, 37% showed depression, and up to 37% had a positive screening for generalized anxiety disorder. Our results showed that the pandemic has particularly affected the group of female Ob-Gyn specialists, with significant higher scores in depression and anxiety scales. Conclusions: As a lesson learned for the future in case of new health emergencies, it would be very important to provide professionals with adequate psychological support, ensuring enough human and material resources, flexible work shifts, and facilities to reconcile work and family-life, especially in the case of female specialists.
Keywords: Pandemia de la COVID-19, 2020-2023 - Aspectos psicológicos; SARS-CoV-2; Mental health; Obstetrics; Gynecology